2021
DOI: 10.3390/jcm10245979
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Metabolic Parameters on Baseline F-18 FDG PET/CT in Predicting Treatment Response and Survival in Paediatric and Adolescent Hodgkin Lymphoma

Abstract: Lymphoma is the third most common paediatric cancer. Early detection of high-risk patients is necessary to anticipate those who require intensive therapy and follow-up. Current literature shows that residual tumor avidity on PET (Positron Emission Tomography) following chemotherapy corresponds with decreased survival. However, the value of metabolic parameters has not been adequately investigated. In this retrospective study, we aimed to evaluate the prognostic value of metabolic and other parameters in paedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Previous studies have indicated that PET volumetric parameters re ecting tumor metabolic burden, such as TMTV and TLG, may provide additional information as prognostic biomarkers for DLBCL [28,29]. Several retrospective studies have analyzed baseline PET metabolic parameters in HL patients, demonstrating that MTV or TLG are robust predictors of treatment response after chemotherapy [30,31]. Parvez et al [32] conducted a retrospective analysis of 82 NHL patients who underwent PET/CT and found that metabolic tumor parameters from [18F] FDG PET/CT could predict treatment response in NHL.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that PET volumetric parameters re ecting tumor metabolic burden, such as TMTV and TLG, may provide additional information as prognostic biomarkers for DLBCL [28,29]. Several retrospective studies have analyzed baseline PET metabolic parameters in HL patients, demonstrating that MTV or TLG are robust predictors of treatment response after chemotherapy [30,31]. Parvez et al [32] conducted a retrospective analysis of 82 NHL patients who underwent PET/CT and found that metabolic tumor parameters from [18F] FDG PET/CT could predict treatment response in NHL.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective investigation conducted on children diagnosed with HIV-related lymphoma found the same findings. According to Reed et al's study [34], HIV infection level as well as therapy response on PET were significant independent predictors of PFS (P = 0.036 and P = 0.001, respectively). Conversely, no metabolic characteristic was predictive of overall survival (OS) or PFS.…”
Section: F-fdg Pet/ctmentioning
confidence: 93%
“…In contrast, none of the metabolic parameters was significantly predictive of either PFS or overall survival (OS). Unlike in the adult research, the baseline total MTV was considered as a significant predictor of treatment response (p=0.017) ( 55 ).…”
Section: Pet For Response Evaluation and Prognostic Predictionmentioning
confidence: 99%